Epigenetic profiling with ultralow DNA amounts. (March 2018) - Lin, Feng-Mao; Chien, Shu; Chen, Zhen
A microfluidic device powers DNA-methylome sequencing of CpG islands and promoter regions, with minimal sample loss.